Κινηματική ανάλυση και σχεδιασμός επίπεδων τροχών με χρήση της Ενοποιημένης Θεωρίας Οδοντώσεων - Μπεζμέρτης, Φίλιππος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου. Εργαστήριο Στοιχείων Μηχανών, 2015)
Face gear drives with a spur involute as they are considered to be. That is the main subject of this diploma thesis. These gears are not as known to many people but they are used in a lot of demanding applications. In general, there are many ways to develop the geometry of these gears but we mostly choose the ‘’Unified Theory of Gearing’’. This theory can produce directly the profile of the mating gear from the profile of the generator with simple analytical equations. Mainly, searching for these gears is not that easy, because the bibliography for this subject is quite few. For that reason, it becomes necessary, that the creation of these different pairs of gears in the software Kissoft. That is really meaningful, because the geometries seemed to work and the different problems that they facing were seen. After that, an effort was made to develop these face gears by our own means. The equations of transformation in Excel were introduced , in which the points of mating surface were calculated. Furthermore, these points became the surface of the face gear in the 3D CAD software Solidworks. In the end, different pairs of gears were created(spur, helical, off-axis and asymmetric gears as generators) ,which were compared with the pairs of gears generated from different theories.